Diversidad y distribución de los crustáceos estomatópodos y decápodos en el estuario del río Gallegos (Santa Cruz, Argentina) - Eduardo R. Torres (Revista de Biología Tropical, 2007)
Diversity and distribution of stomatopod and decapod crustaceans in the estuary of Gallegosriver (Santa Cruz-Argentina). We studied the diversity and distribution of stomatopod and decapod crustaceansfrom the estuary of Gallegos River, Argentina. Decapods were found at all stations, while stomatopodsand anomurans were found only at the exterior station. There was a marked difference in diversity, the exteriorstation being more diverse. A total of six species were found (five decapods and one stomatopod), a low valuewhen compared with the surrounding sea. Abundance was variable at stations, depending on the type of bottom.Rev. Biol. Trop. 55 (Suppl. 1): 113-120. Epub 2007 June, 29.